IMPLEMENTASI WEBGIS UNTUK NAVIGASI RUTE DAN MONITORING HYDRANT PEMADAM KEBAKARAN DI KOTA MEDAN - Rizky Afriansyah; Tantri Hidayati Sinaga (P3M STMIK Profesional Makassar, 2025)
Firefighting operations in Medan City still face significant challenges in locating and monitoring the condition of fire Hydrants: out of 118 Hydrant points, only 23 are documented as operational and just 6 are fully functional. This study aims to design and implement a web‑based WebGIS for the fastest route navigation to the nearest Hydrant and real‑time Hydrant condition Monitoring, employing an iterative Prototype methodology. The system is built using PHP & MySQL on the backend, Leaflet.js for interactive mapping and Routing, and AJAX for seamless data Updates. Functional testing (black‑box) confirms all modules Admin Login, Hydrant CRUD, “Nearest Hydrant” Routing, status Updates, and map Refresh operate as expected with average AJAX response times of 0.3 - 0.5 seconds and map load times under 1.5 seconds for 200 points. Field accuracy tests reveal a coordinate deviation of ± 3 meters, while Hydrant search time is reduced from an average of 2 minutes manually to approximately 15 seconds digitally. The responsive interface supports both desktop and mobile access, optimally serving Admin and Field Officer needs. Thus, the system demonstrably enhances firefighting response efficiency and Hydrant data accuracy in Medan City.